Network-based pharmacology and molecular docking exploring the "Bupleuri Radix-Scutellariae Radix" mechanism of action in the viral hepatitis B treatment. Issue 48 (2nd December 2022) - Long, Piao; Xia, Yu; Yang, Yuying; Cao, Jianzhong
Abstract : Viral hepatitis B is caused by the hepatitis B virus, which is characterized by liver lesions. Bupleuri Radix and Scutellariae Radix are the main traditional medicine pairs with remarkable efficacy in hepatitis B. However, their molecular mechanisms are incompletely understood. The main active components of Bupleuri Radix and Scutellariae Radix, as well as therapeutic targets for the treatment of hepatitis B, were identified through network pharmacology techniques. We identified viral hepatitis B targets using the GeneCards, online mendelian inheritance in man, and therapeutic target databases. We discovered the active components of Bupleuri Radix and Scutellariae Radix as well as therapeutic targets using the encyclopedia of traditional Chinese medicine, HERB, traditional Chinese medicine systems pharmacology database, and a bioinformatics analysis tool for molecular mechanism of traditional Chinese medicine databases. VENNY obtained the intersections. Cytoscape and STRING were used to create the "active ingredient-potential target" network and protein interaction network. The DAVID database was used to enrich GO and KEGG pathways. The results were confirmed using the molecular docking method. There were 1827 viral hepatitis B targets, and 37 active ingredients for Bupleuri and Scutellariae Radix, with the main components being quercetin, wogonin, baicalein, and kaempferol. Tumor necrosis factor (TNF), mitogen-activated protein kinase 3 (MAPK3), interleukin-6 (IL-6), vascular endothelial growth factor A, cysteinyl aspartate specific proteinase 3, transcription factor AP-1 (JUN), RAC-alpha serine/threonine-protein kinase, and cellular tumor antigen p53 are among the 78 common targets of Bupleuri Radix and Scutellariae Radix intervention in viral hepatitis B. KEGG enrichment resulted in 107 pathways, including cancer, hepatitis B, and TNF signaling pathways. According to the molecular docking technique, quercetin, wogonin, baicalein, and kaempferol had strong binding activities with TNF, MAPK3, and IL-6. In this study, we initially identified various molecular targets and multiple pathways involved in hepatitis B treatment with Bupleuri Radix and Scutellariae Radix.